2015
DOI: 10.1093/jmammal/gyv165
|View full text |Cite
|
Sign up to set email alerts
|

Roadkills as a complementary information source for biological surveys using rodents as a model

Abstract: Roads affect wildlife in many ways, with roadkills probably the most conspicuous. In Mexico, there is increasing interest in this effect on wildlife. Together, richness and abundance can be used to predict trends for wild populations, and our study analyzes these variables for rodents killed by vehicles and trapped along a 14-km stretch of an A-type roadway in Veracruz, Mexico, from June 2010 to March 2011. Our study area had 2 habitat types: shrubland on lava flow and grassland. Over the course of the study, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 37 publications
1
11
0
Order By: Relevance
“…Of these predictors, area was most important (based on scaled effect sizes in Table 4). Assuming that living diversity is representatively sampled by WVCs (as observed by González-Gallina et al, 2015 andCanova &Balestrieri, 2019), and given that the observed species-area effect fits long-established expectations (Rosenzweig, 1995), then results here may indicate a similar species-area relationship for living wildlife diversity in the parks. Tests of that relationship must await more complete inventories of wildlife living in Florida State Parks, but results here suggest a strong biogeographic effect on habitat "islands" in the midst of rapid human population growth and land use.…”
Section: What Best Explains Wvc Differences Among Parks?supporting
confidence: 58%
See 2 more Smart Citations
“…Of these predictors, area was most important (based on scaled effect sizes in Table 4). Assuming that living diversity is representatively sampled by WVCs (as observed by González-Gallina et al, 2015 andCanova &Balestrieri, 2019), and given that the observed species-area effect fits long-established expectations (Rosenzweig, 1995), then results here may indicate a similar species-area relationship for living wildlife diversity in the parks. Tests of that relationship must await more complete inventories of wildlife living in Florida State Parks, but results here suggest a strong biogeographic effect on habitat "islands" in the midst of rapid human population growth and land use.…”
Section: What Best Explains Wvc Differences Among Parks?supporting
confidence: 58%
“…On the other hand, SR may be more stable than abundance-based measures given varied sampling among parks through the years. For example, WVC surveys efficiently estimate SR of living wildlife, compared to more intensive sampling (Canova & Balestrieri, 2019;González-Gallina et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…D'Amico et al (46) has highlighted the relevance of phenology as the most important factor affecting temporal roadkill patterns in small mammals as well as Canal et al (63) showed that these kinds of patterns were repeated over years and ecoregions in a same region as Andalucía. Therefore, it is likely that our results may be repetitive in similar conditions of environments, road features and hare population status, showing the existence of an unknown hare mortality rate and giving them relevance for the species management (73).…”
Section: Implications Of the Hare's Roadkill On Its Conservationmentioning
confidence: 92%
“…Road traffic does not only impact snakes, but also other animals (Ashley and Robinson 1996;Glista et al 2007;Baxter-Gilbert et al 2015;Ciolan et al 2017). The high number of mortalities from different animal groups has permitted road mortalities to be employed as study material for feeding ecology (Drygala and Zoller 2013; Kolenda et al 2019), phylogeography (Grill et al 2009;Horcajada et al 2018), temporal trends in populations (Meek 2020) and faunistic studies (Gonzáles-Gallina et al 2016;Teodor et al 2019).…”
Section: Introductionmentioning
confidence: 99%